Analyzing the Playstation Network Hack Through PMBOK Lenses - Faidzli, Anastazry; Duurgashini P Balan,; Nuvanehsan M Selvan,; Jonathan Joseph,; Mathushini Kathiraveloo,; Thaswin Muralikaran,; Vimalla Subramaniam,; Danish Hossman Abd Rahman,; Siti Hajar Arbain, (Applied Information Technology And Computer Science, 2023)
The PlayStation Network outage (sometimes referred to as the PSN Hack) was the result of an "external intrusion" on Sony's PlayStation Network and Qriocity services, in which personal details from approximately 77 million accounts were compromised and prevented users of PlayStation 3 and PlayStation Portable consoles from accessing the service. This report dives into the many facets of the PSN hack, exploring the circumstances that led to the breach, the ramifications, and the responses. This case study highlights the need to incorporate these knowledge domains into complete risk mitigation and recovery strategies, reinforcing the importance of proactively handling and aligning stakeholders' interests. The focus of the report will be on how each of these knowledge domains contributed to considering, dealing with, and eventually recovering from the PlayStation Network attack. In the context of a global-scale data breach, this research serves as a sharp reminder of the consequences of poor procurement management, insufficient risk assessment, quality control, and stakeholder involvement. The insights gathered from this case study will provide significant lessons for organizations across industries, underscoring the crucial relevance of rigorous management practices in protecting the interests of all stakeholders against unanticipated dangers.